2020
DOI: 10.1159/000506404
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Depression on Weight Variation after Bariatric Surgery: A Three-Year Observational Study

Abstract: Introduction: The association between obesity and depression has been repeatedly established. However, little is known about the impact that the diagnosis of depression before bariatric surgery (DDBS) may have on weight loss. Objective: To evaluate the impact of DDBS on weight outcomes. Methods: Retrospective study of patients submitted to BS. Patients with no weight, no current medication data, or those submitted to revision surgery were excluded. Patients were considered to have DDBS based on taking antidepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 28 publications
0
13
1
Order By: Relevance
“…Surgery has a more positive impact on the depressive disorders than anxiety disorders (de Zwaan et al, 2011), but preoperative symptoms also likely affect the results of the surgical methods. Preoperative depression is also associated with lower postoperative weight loss (Pedro et al, 2020). Although MOR availability is associated with depressive and anxious symptoms (Nummenmaa et al, 2020), we observed no association between depressive and anxiety symptoms and weight loss.…”
Section: Discussioncontrasting
confidence: 61%
“…Surgery has a more positive impact on the depressive disorders than anxiety disorders (de Zwaan et al, 2011), but preoperative symptoms also likely affect the results of the surgical methods. Preoperative depression is also associated with lower postoperative weight loss (Pedro et al, 2020). Although MOR availability is associated with depressive and anxious symptoms (Nummenmaa et al, 2020), we observed no association between depressive and anxiety symptoms and weight loss.…”
Section: Discussioncontrasting
confidence: 61%
“…Surgery has a more positive impact on the depressive disorders than anxiety disorders ( 34 ), but preoperative symptoms also likely affect the results of the surgical methods. Preoperative depression is also associated with lower postoperative weight loss ( 35 ). Although MOR availability is associated with depressive and anxious symptoms ( 36 ), we observed no association between depressive and anxiety symptoms and weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…The BES is a 16-item self-report questionnaire assessing the severity of binge eating behavior. Total scores range from 0 to 46 with cut-off scores of possible (18)(19)(20)(21)(22)(23)(24)(25)(26) and probable (≥ 27) BED (31). Cronbach's alpha in the present sample was 0.91.…”
Section: Psychometric Instrumentsmentioning
confidence: 80%
“…the period of rapid and drastic weight loss that begins immediately after surgery and continues for six to 12 months), differences in patients' weight loss trajectories became apparent (14,15). More precisely, it was reported that either binge eating disorders (BED) or major depression consistently exhibited their negative effect on body mass index (BMI) evolution at least two years after surgery (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%